2020
DOI: 10.4103/ijcm.ijcm_336_19
|View full text |Cite
|
Sign up to set email alerts
|

Population attributable risk of tuberculosis vulnerabilities in Kerala, India

Abstract: Background: A robust disaggregated understanding of the determinants of tuberculosis (TB) in each local setting is essential for effective health system and policy action to control TB. Objectives: The objective of the study was to identify population attributable risk (PAR) for TB disease based on the locally available evidences for Kerala, India. Methods: Systematic review was done for risk factors of TB in the state. The second set of sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Undernutrition, which affects 6.90 million people globally, is on the rise, negatively impacts people's immune systems, and is a risk factor in TB, although it is described as an individual's intake of insufficient calories and nutrients to meet their need to maintain good health. 8,32,73,74 Several studies have found that adults aged 15-49 years with a low body mass index (BMI) (<18.50 kg/m 2 ) are more likely to develop TB, experience poor treatment outcomes, and have a higher risk of death. 9,28,31,37,38,41,73,74 Rural areas, scheduled castes and tribes, other socially and economically backward classes, states with higher levels of poverty, and migrant workers all have high rates of undernourishment, which increases their risk of developing TB.…”
Section: Undernutrition and Tuberculosismentioning
confidence: 99%
See 1 more Smart Citation
“…Undernutrition, which affects 6.90 million people globally, is on the rise, negatively impacts people's immune systems, and is a risk factor in TB, although it is described as an individual's intake of insufficient calories and nutrients to meet their need to maintain good health. 8,32,73,74 Several studies have found that adults aged 15-49 years with a low body mass index (BMI) (<18.50 kg/m 2 ) are more likely to develop TB, experience poor treatment outcomes, and have a higher risk of death. 9,28,31,37,38,41,73,74 Rural areas, scheduled castes and tribes, other socially and economically backward classes, states with higher levels of poverty, and migrant workers all have high rates of undernourishment, which increases their risk of developing TB.…”
Section: Undernutrition and Tuberculosismentioning
confidence: 99%
“…1,2,[16][17][18][19][20][21][22] Co-morbidities that weaken the immune system and increase the risks of TB infection in people over a short period of time include undernutrition, diabetes, HIV, tobacco use, smoking, and alcohol consumption. 2,[21][22][23][24][25][26][27][28][29][30][31][32] M. tuberculosis also has a diverse pattern of region-specific prevalence and susceptibility, genetic mutation over time, space, and environment. 23,33,34 Nearly one in every two TB patients' household contacts has latent TB, and the severity of the infection is related to the age of the household contacts.…”
Section: Introductionmentioning
confidence: 99%
“…Common risk factors (vulnerabilities) for TB in Kerala were listed. The process undertaken for identifying TB risk factors and estimating their relative risks through a systematic literature review of locally available studies and programmatic data have been described elsewhere [7]. Weighted scores were assigned to the vulnerabilities based on the estimates of relative risk [7,8].…”
Section: Conceptmentioning
confidence: 99%
“…The process undertaken for identifying TB risk factors and estimating their relative risks through a systematic literature review of locally available studies and programmatic data have been described elsewhere [7]. Weighted scores were assigned to the vulnerabilities based on the estimates of relative risk [7,8]. The use of an expert group consensus has been widely accepted as a method for providing a basis for decision-making when there is limited evidence or when there are doubts about the applicability of evidence that has been generated from other populations.…”
Section: Conceptmentioning
confidence: 99%
See 1 more Smart Citation